Reduced order controllers for Burgers' equation with a nonlinear observer - Atwell, Jeanne A.; Borggaard, Jeffrey T.; King, Belinda B. (Zielona Góra: Uniwersytet Zielonogórski)
A method for reducing controllers for systems described by partial differential equations (PDEs) is applied to Burgers' equation with periodic boundary conditions. This approach differs from the typical approach of reducing the model and then designing the controller, and has developed over the past several years into its current form. In earlier work it was shown that functional gains for the feedback control law served well as a dataset for reduced order basis generation via the proper orthogonal decomposition (POD).
Keywords: Burgers' equation; reduced order controllers; proper orthogonal decomposition; minmax control design; stabilized finite elements